Acute haemorrhagic oedema of infancy in a 5‐week‐old boy referred to the Child Protection Unit. (23rd December 2013) - Hawkrigg, Sharon; Johnson, Alice; Flynn, James; Thom, Graham; Wright, Helen
Abstract We describe the case of a 5‐week‐old infant boy presenting with purpura and oedema to both hands and torso. He was otherwise well, with no antecedent history of illness or trauma. Laboratory investigations were within normal limits. A review by the Child Protection Unit was organised during his admission for consideration of inflicted trauma as a cause of the lesions; this was felt most unlikely. A clinical diagnosis, following a dermatology consultation, of acute haemorrhagic oedema of infancy (AHO) was made.